THE IMPLEMENTATION OF “CONNECTING WORDS” GAME TO TEACH SPEAKING DESCRIPTIVE FOR SEVENTH GRADERS OF SMPN 1 TURI (RETAIN, 2017)
THE IMPLEMENTATION OF “CONNECTING WORDS” GAME TO TEACH SPEAKING DESCRIPTIVE FOR SEVENTH GRADERS OF SMPN 1 TURI Yusuf Dwi Prasetyo English Education, Faculty of Languages and Arts, State University of Surabaya yusufprasetyo@mhs.unesa.ac.id Abstrak Berbicara adalah satu dari empat kemampuan yang vital dalam bahasa inggris; namun, dalam mengajar berbicara tidaklah semudah yang dibayangkan, apalagi dengan ditambah kebiasaan siswa yang cenderung pasif. Dengan memakai game “Connecting Words”, guru dapat mengajak siswa untuk aktif menggunakan kemampuan berbicaranya dengan kegiatan yang menyenangkan serta memberikan kesempatan untuk memakai dan mengasah kemampuan mereka tanpa harus khawatir dengan ketersediaan media. Tujuan dari peneltian adalah untuk menjelaskan bagaimana game “Connecting Words” diterapkan untuk mengajar berbicara dalam konteks teks deskriptif bagi anak kelas tujuh SMPN 1 Turi dan bagaimana siswa menanggapinya. Penelitian ini memakai metode deskriptif kualitatif serta memakai lembar observasi untuk mencatat aktivitas dalam kegiatan belajar mengajar, disertai interview dengan guru untuk menambah data; dan beberapa siswa diinterview untuk dimintai pendapatnya tentang penerapan game “Connecting Words” dalam proses pembelajaran. Hasil menunjukkan bahwa guru mampu menerapkan game kedalam kegiatan pembelajaran dalam konteks berbicara teks deskriptif. Respon dari siswa yang dari interview menunjukkan bahwa mereka cukup senang dengan penerapan gamenya; mereka setuju kalau dengan memeaki game, mereka diberi kesempatan untuk berbicara dan berlatih teks deskriptif serta gamenya memberi kesan baik dalam merubah keadaan kelas dari kegiatan pembelajaran yang membosankan. Kata Kunci: Berbicara, Game, Game Connecting Words, Teks Deskriptif Abstract Speaking is one of four important English skills; however, teaching speaking is not exactly easy with the students often being passive. By using “Connecting Words” game, teacher can encourage the students to actively use their speaking skill with fun and engaging activity, which also give them opportunity to use and hone their skill, without worrying about media. The goals of this study are to describe the implementation of the “Connection Words” game in teaching spoken descriptive text for the seventh graders of SMPN 1 Turi and to describe the students’ responses towards the game. This study uses qualitative descriptive research. Through observation notes the researcher described the teacher and student activities during the class, followed by interview with the teacher to get more data. Then several students were interviewed for their opinion toward the implementation of “Connection Words” game to teach spoken descriptive text. The result showed that the teacher managed to implement the game into teaching learning activity to teach spoken descriptive text. Students’ responses obtained through interview indicated that they were fairly positive with the game. They agreed that the game gave them opportunity to speak and practice on descriptive text as well as providing good change of atmosphere to break the monotony in teaching learning activity. Keywords: Speaking, Games, Connecting Words Game, Descriptive Text.